A Study On The Flow Characteristic In The Artificial Riffle Zone - Li, Bai Hao (Universiti Sains Malaysia, 2021)
With the rapid development of the world as well as in Malaysia, many natural rivers have been destroyed due to urbanisation. Urban modernisation has brought changes to the natural environment; therefor'e, people should ameliorate the damaged river using artificial riffle structures. The artificial riffle structure helps restore the shape of the river, water quality, and aquatic habitat. Therefore, in this thesis, the characteristics of flow in the artificial riffle zone are studied with numerical modeling method. Numerical modeling is a convenient tool for studying flow in artificial riffle zone. As a reliable commercial software, the Flow-3D model is used to simulate flow over the artificial riffle zone. The simulation was carried out with different flow Froude numbers to evaluate the turbulent kinetic energy in the artificial riffle zone. Numerical simulation results show that the is distinct difference in the turbulent kinetic energy at different flow depths in the artificial riffle zone.